1997
DOI: 10.1097/00000374-199709000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Catalase Mediates Acetaldehyde Formation from Ethanol in Fetal and Neonatal Rat Brain

Abstract: Fetal ethanol (E) exposure has well documented deleterious effects on brain development, yet it is uncertain if the neurotoxicity of maternal E consumption is generated by E itself, by its primary metabolite acetaldehyde (AcHO), or both. The current studies present evidence that homogenates of immature rat brains can generate AcHO via a catalase (CAT)-mediated reaction and that AcHO may be produced in vivo by this system. Homogenates of day 19 fetal rat brain were incubated with E (50 mM). When incubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Catalase immunoreactivity and activity were found to be higher in the neonatal rat than in the adult (Del Ma3stro and McDonald, 1987;Moreno et al, 1995;Hamby-Mason et al, 1997). In contrast, GPx was shown to undergo a 70% increase in activity in rat whole brain between birth and adulthood (Brannan et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Catalase immunoreactivity and activity were found to be higher in the neonatal rat than in the adult (Del Ma3stro and McDonald, 1987;Moreno et al, 1995;Hamby-Mason et al, 1997). In contrast, GPx was shown to undergo a 70% increase in activity in rat whole brain between birth and adulthood (Brannan et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…48 Further studies have demonstrated that both Genetic polymorphism in ethanol metabolism E Quertemont astrocytes in culture and rat brain homogenates are able to produce biologically significant concentrations of acetaldehyde from perfused ethanol. 34,[49][50][51] These studies have also shown that catalase plays a critical role in this process, as the addition of various catalase inhibitors to brain homogenates reduces acetaldehyde accumulation after ethanol perfusion. 34,50 However, other pathways might also be involved in ethanol metabolism and acetaldehyde production within the brain.…”
Section: Aldehyde Dehydrogenasementioning
confidence: 91%
“…Some of the acetaldehyde present in the brain can be the result of acetaldehyde molecules that are produced peripherally and then reach the brain, although it is difficult for acetaldehyde to cross the blood-brain barrier because of the metabolic barrier presented by large concentrations of ALDH (Hunt, 1996;Quertemont and Tambour, 2004). Nevertheless, some acetaldehyde can be directly formed in the brain through the actions of catalase (Aragon et al, 1992b;Reddy et al, 1995;Zimatkin and Lindros, 1996;Hamby-Mason et al, 1997;Eysseric et al, 1997;Zimatkin et al, 1998). The notion that ethanol metabolism in the brain is important for some of the behavioral effects of ethanol is supported by the reports that manipulations of catalase activity exert a powerful effect on ethanol-induced behavior (Aragon et al, 1992a;Aragon and Amit, 1993;Correa et al, 1999aCorrea et al, , b, 2000Correa et al, , 2001Correa et al, , 2004aSanchis-Segura et al, 1999a-c;Pastor et al, 2002).…”
Section: Role Of Ethanol Metabolismmentioning
confidence: 99%